2022
DOI: 10.3390/insects13100908
|View full text |Cite
|
Sign up to set email alerts
|

Conservation Biological Control of Codling Moth (Cydia pomonella): Effects of Two Aromatic Plants, Basil (Ocimum basilicum) and French Marigolds (Tagetes patula)

Abstract: The addition of flowering companion plants within or around crop fields is a promising strategy to strengthen pest regulation by their natural enemies. Aromatic plants are frequently used as companion plants, but their effects on natural enemies remain unclear under field conditions. Here, we evaluated the effects of two aromatic plant species on the parasitism of the codling moth (Cydia pomonella) and the recruitment of predatory arthropods (spiders, earwigs) in a factorial field experiment. Apple trees were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The combined yield advantage in terms of land equivalent ratio (LER), area time equivalent ratio (ATER) and LUE indices was the greatest for 1:4 for the rosemary, followed by 1:4 for the sweet basil intercropping pattern arrangement [58]. The sole focus of a one-year study conducted in a semi-urban field area in France was to investigate the biological control of the codling moth Cydia pomonella L. (a pest causing high damage to various perennial crops worldwide, particularly to apple orchards) by intercropping apple with sweet basil and French marigold (positioned in pots) [59]. Results of the study showed that intercropping with basil increased codling moth parasitism, but did not affect arthropod predator abundances, whereas intercropping with French marigold, decreased both pests and predators (Table 1).…”
Section: No Information Providedmentioning
confidence: 99%
“…The combined yield advantage in terms of land equivalent ratio (LER), area time equivalent ratio (ATER) and LUE indices was the greatest for 1:4 for the rosemary, followed by 1:4 for the sweet basil intercropping pattern arrangement [58]. The sole focus of a one-year study conducted in a semi-urban field area in France was to investigate the biological control of the codling moth Cydia pomonella L. (a pest causing high damage to various perennial crops worldwide, particularly to apple orchards) by intercropping apple with sweet basil and French marigold (positioned in pots) [59]. Results of the study showed that intercropping with basil increased codling moth parasitism, but did not affect arthropod predator abundances, whereas intercropping with French marigold, decreased both pests and predators (Table 1).…”
Section: No Information Providedmentioning
confidence: 99%
“…Among the different generalist predators that may play a role in the control of C. pomonella [ 29 ], ground-dwelling ants can prey upon last instar larvae and pupae [ 18 ]. More recently, field data suggested that trees visited more intensively by ants may suffer less damage to their fruits by the moths [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous Integrated Pest Management (IPM) techniques, including mating disruption [25][26][27][28], attract-and-kill [29], or sterile insect technique [30,31], and many other environmentally friendly strategies that can be implemented in the modern codling moth management [32,33]. Although all these techniques are available, growers mostly resort to chemical measures [18,34], which has led to the emergence of insecticide resistance, making codling moth control much more difficult [2,[34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%